Ethical Decision Making Based On The Literature Review Of Ford & Richardson 1962 - 1993 - Suryadi Winata; Agus Kusnawan; Limajatini Limajatini; Eso Hernawan (Primanomics : Jurnal Ekonomi & Bisnis, 2020)
The objective of this study is to review ethical judgments of Accountants from 1962 to 1993. The research uses the literature review of Ford and Richardson, 1994 on the empirical ethical decision making. The results show that ethical factors individual, situational, organizational influencing ethical decision making (EDM) are organizational effects, organizational size, and peer group influence and Machiavellinism is also the significant factor in individual EDM